2017
DOI: 10.1007/s13398-017-0392-9
|View full text |Cite
|
Sign up to set email alerts
|

On the non-triviality of certain spaces of analytic functions. Hyperfunctions and ultrahyperfunctions of fast growth

Abstract: Abstract. We study function spaces consisting of analytic functions with fast decay on horizontal strips of the complex plane with respect to a given weight function. Their duals, so called spaces of (ultra)hyperfunctions of fast growth, generalize the spaces of Fourier hyperfunctions and Fourier ultrahyperfunctions. An analytic representation theory for their duals is developed and applied to characterize the nontriviality of these function spaces in terms of the growth order of the weight function. In partic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…We introduce the following set of conditions on Mp and Ap: MpandApsatisfyfalse(M.1false)andfalse(M.2false),p!MpAp,andscriptS(Ap)(Mp)-0.16emtrue(Rdtrue)isnon-trivial.A sufficient condition for the non‐triviality of scriptS(Ap)(Mp)-0.16emtrue(Rdtrue) is p!σMp and p!τAp for some σ,τ>0 with σ+τ>1 [, p. 235]. Other non‐triviality conditions can be found in . Under the general conditions , we have the ensuing properties: (i)The Fourier transform is a topological isomorphism from scriptS*-0.16emtrue(Rdtrue) onto scriptS*-0.16emtrue(Rdtrue), where we fix the constants in the Fourier transform as follows 0truescriptF(φ)(ξ)=t...…”
Section: Preliminariesmentioning
confidence: 99%
“…We introduce the following set of conditions on Mp and Ap: MpandApsatisfyfalse(M.1false)andfalse(M.2false),p!MpAp,andscriptS(Ap)(Mp)-0.16emtrue(Rdtrue)isnon-trivial.A sufficient condition for the non‐triviality of scriptS(Ap)(Mp)-0.16emtrue(Rdtrue) is p!σMp and p!τAp for some σ,τ>0 with σ+τ>1 [, p. 235]. Other non‐triviality conditions can be found in . Under the general conditions , we have the ensuing properties: (i)The Fourier transform is a topological isomorphism from scriptS*-0.16emtrue(Rdtrue) onto scriptS*-0.16emtrue(Rdtrue), where we fix the constants in the Fourier transform as follows 0truescriptF(φ)(ξ)=t...…”
Section: Preliminariesmentioning
confidence: 99%
“…for some ε > 0; see also [7,Proposition 4.3], where it is moreover shown that this rate of decay on a strip is essentially best possible. Define h : R → C by…”
Section: Optimal Decay For Functionsmentioning
confidence: 98%
“…[11, p. 235]. Other non-triviality conditions can be found in [5]. If a weight function ω is pp!q-admissible, then Assumption 3.1 is fulfilled for M p and ω, whenever M p is weight sequence that satisfies pM.1q and plog pq p ă M p , as follows from [ In the rest of this section, we fix a weight sequence M p satisfying pM.1q and pM.2q 1 and a weight function ω such that Assumption 3.1 holds.…”
Section: The Spaces DL 1 ω and 9 B 1ωmentioning
confidence: 99%